THE STATE OF FAMILY FARMERS IN THREE COUNTRIES OF CENTRAL AMERICA - Shahin, Hala; Pessanha Penha-Lopes, Gil (REVISTA DE AGRICULTURA, 2020)
This study aims to describe the state of family farmers in Panama, Costa Rica, and El Salvador, and to examine the differences between the perspective of the family farmers and the policymakers in this regards. To achieve this aim, 90 in-depth, structured, close-ended interviews were conducted with ninety study participants throughout the fieldwork, 30 participants in each country divided equally into policymakers and family farmers. The obtained results confirm that family farmers are facing challenges that limit their production capacity due to unequal access to production resources, unjust distribution of power, and lack of supportive policies. Developing the right policies to strengthen family farmers, improve the efficiency of the rural organization, and guarantee rural generation sustainability, will help to enhance the performance of family farmers in producing sustainable, culturally approved food and improve food and nutrition security.